Gobierno abierto y su incidencia en la operatividad de la administraciòn pública del gobierno autónomo descentralizado municipal del cantón Mocache, año 2022 - Monserrate Espinoza, Sandra Jhonyla (2023)
An open government is a new management model, giving rise to increased participation, transparency in public administration, technological innovation and accountability. The objective of this work is to evaluate the impact of open government on the operation of the public administration of the GADMM, in addition, it was conceptually and theoretically based on what refers to open government, operation, public administration and its different elements. Citing important theorists, such as Charles Bonnin, Oscar Oszlak, Peter Drucker, Galván, among others. The applied methodology was based on a mixed approach (quantitative and qualitative). To provide sustainability and veracity in the establishment of conclusions and results, instruments such as surveys were used, which were directed at the population of Mocache, also at experts on the topic raised, and interviews directed at public officials belonging to the GADMM. It should be noted that the results obtained show the main challenges or barriers identified to achieve an effective open government, with 50.3% being the obstinacy to change on the part of government entities, with 25.8% being the lack of resources and capabilities. to implement open government policies, and the lack of awareness about the benefits of open government. Finally, precise conclusions were reached that show the importance of addressing these barriers through training, promoting civic education, the use of digital platforms and improving the dissemination of relevant information to promote citizen participation and dialogue.